Penerapan Metode Pembelajaran Berbasis Masalah untuk Meningkatkan Keterampilan Pemecahan Masalah Siswa Sekolah Dasar - rasimah, emeh; yaya, yaya (Papanda Publisher, 2022)
This research aims to explore the impact of implementing problem-based learning method on the problem-solving skills of Elementary School (SD) students. Through a qualitative approach involving observation, interviews, and document analysis, data were collected from teachers and students at SDN Salawana I. The analysis results indicate that the implementation of the problem-based learning method has a positive impact on student engagement, collaboration among students, and the development of problem-solving skills. Students show higher enthusiasm in learning when engaged in problem-solving relevant to their daily lives, while teachers report a significant improvement in students' ability to identify problems and formulate solutions. The practical implications of these findings support innovative approaches in elementary-level learning, emphasizing the importance of student engagement in the learning process. However, challenges in implementing this method also need to be considered, including infrastructure readiness and teacher training. This research contributes significantly to our understanding of the potential of problem-based learning methods in enhancing the problem-solving skills of SD students, while highlighting the importance of ongoing support in its implementation.